The Influence of Project-Based Learning in Creating AI-Driven Animation Videos on Early Childhood Discipline - Widiastuti, Reski Yulina; Pramesti, Maulidyah Zahra Galuh; Afifah, Nur Habibah; Khotimah, Azkia Khusnul; Driyaningsih, Ari (LPPI Yayasan Almahmudi bin Dahlan, 2024)
Children learn discipline, defined as appropriate and approved behavior, from an early age to foster positive character development and prepare them for their next development stage. This research aims to find out how much influence the AI project-based learning model for making animated videos has on early childhood discipline. This research employed a quantitative approach using a one-group pretest-posttest design, focusing on a sample of 19 children between the ages of 5 and 6 years. The research collected data using pretest and posttest data observation instruments and implemented project-based learning to create AI-based animated videos. Data analysis used the paired sample T-test and obtained a T value of 8.244 > T table 2.109, while a significance value of 0.000 < 0.005 indicated that Ha was accepted and H0 was rejected. This proves that the application of the project-based learning model to making AI-based animated videos influences the discipline of children aged 5–6 years at Kindergarten Dharma Indri 1 Jember. The research results show that project-based learning involves creating animated videos using AI, is very suitable for young children and can significantly improve children's discipline.